IMPLEMENTASI MUHADATSAH YAUMIYYAH DALAM MENINGKATKAN MAHARAH KALAM - Yeniati Ulfah; Anyes Lathifatul Insaniyah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
Maharah kalam is one of the language skills to be achieved in learning Arabic. This study aims to determine the implementation of muhadatsah yaumiyah in increasing maharah kalam at Madrasah Diniyah Al-Amiriyah Pondok Pesantren Darussalam Blokagung Banyuwangi. This research is a qualitative descriptive research with data collection techniques of observation, interviews, and documentation. The results of this study are first, that all students are accustomed to speaking Arabic when attending Arabic lessons at Madrasah Diniyah. Second, students become more confident when speaking Arabic without feeling embarrassed and afraid of being wrong. Third, students are increasingly diligent in memorizing mufradat every day. And fourth, students always practice muhadatsah so that they become more fluent and fluent when speaking, so that students are spontaneously able to communicate in Arabic anywhere and anytime.